2020
DOI: 10.3390/plants9040523
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Structural Variants in Two Novel Genomes of Maize Inbred Lines Possibly Related to Glyphosate Tolerance

Abstract: To study genetic variations between genomes of plants that are naturally tolerant and sensitive to glyphosate, we used two Zea mays L. lines traditionally bred in Poland. To overcome the complexity of the maize genome, two sequencing technologies were employed: Illumina and Single Molecule Real-Time (SMRT) PacBio. Eleven thousand structural variants, 4 million SNPs and approximately 800 thousand indels differentiating the two genomes were identified. Detailed analyses allowed to identify 20 variations within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
(83 reference statements)
0
10
1
Order By: Relevance
“…Additionally, two out of seven genes in the shikimate pathway were differentially methylated as a result of the herbicide stress. Herein, we did not detect changes in the methylation pattern in genes encoding shikimate pathway enzymes; however, previous changes in the coding sequences of two shikimate pathways enzymes (bifunctional 3-dehydroquinate dehydratase/ shikimate dehydrogenase and chorismate synthase) in the two tested Z. mays lines (TL and SL) were detected (Mahmoud et al 2020).…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…Additionally, two out of seven genes in the shikimate pathway were differentially methylated as a result of the herbicide stress. Herein, we did not detect changes in the methylation pattern in genes encoding shikimate pathway enzymes; however, previous changes in the coding sequences of two shikimate pathways enzymes (bifunctional 3-dehydroquinate dehydratase/ shikimate dehydrogenase and chorismate synthase) in the two tested Z. mays lines (TL and SL) were detected (Mahmoud et al 2020).…”
Section: Discussioncontrasting
confidence: 74%
“…Previously, it was shown that herbicidal stress influences miRNA expression (Żywicki et al 2015) and that some of the traits related to herbicide resistance may be encoded in the genome (Mahmoud et al 2020). Here, we focused our efforts on analyzing the influence of herbicidal stress on changes in DNA methylation in the same two Z. mays lines, which are differentially susceptible to the systemic herbicide Roundup®.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations